Wawasan Al-Qur’an tentang Dakwah Dialogis (Kontekstualisasi Metode Dakwah Nabi Ibrahim AS.) - Muhbib Abdul Wahab (LP2M Universitas PTIQ Jakarta, 2016)
Prophets cannot be separated from religious missionary (dakwah) activities. And those missionary endeavors cannot be separated from diversitiy (plurality) and society (al-Mad’u). The diversity itself is universal law that will always exist and develop. Religious missionary gets challenge when faced with plurality of people. Prophet muhammad was faced with such situation when he was in Makkah as well when he was establishing new community in Madinah. Such situation was also faced by his predecessors for instance Prophet Ibrahim. So how did Ibrahim and other prophets face them, What kind of missionary method suits the plurality of society? This study is based on thematis and textolinguistic approach (‘ilm al-lughah al-nashshi) to the verses that relate to story of Ibrahim, (which spread in 25 surahs in Qur’an), from the perpective of his missionary model.